2018
DOI: 10.1111/jgh.14534
|View full text |Cite
|
Sign up to set email alerts
|

Okuda lecture: Challenges of hepatitis B in the era of antiviral therapy

Abstract: Nucleos(t)ide analogs (NAs) are effective, safe, and convenient antiviral therapy to suppress replication of hepatitis B virus, which can be translated into improved long‐term outcome of chronic hepatitis B patients. The current recommended first‐line NAs, namely, entecavir and tenofovir, are largely free from problems of drug resistance. Nonetheless, there are still a few challenges in the era of NA. First, the risk of hepatocellular carcinoma can only be reduced but not eliminated, particularly among cirrhot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
(179 reference statements)
0
5
0
Order By: Relevance
“…Liver biopsy typically shows no fibrosis and minimal inflammation. This can be explained by the relative lack of immune pressure on the virus [9]. Early natural history studies of immunetolerant phase revealed a benign disease course.…”
Section: Current Understanding Of Immune-tolerant Phasementioning
confidence: 99%
“…Liver biopsy typically shows no fibrosis and minimal inflammation. This can be explained by the relative lack of immune pressure on the virus [9]. Early natural history studies of immunetolerant phase revealed a benign disease course.…”
Section: Current Understanding Of Immune-tolerant Phasementioning
confidence: 99%
“…Although the current first-line oral nucleos(t)ide analogues (NAs), such as entecavir (ETV) or tenofovir disoproxil fumarate (TDF), can effectively inhibit hepatitis B virus (HBV) replication, HCC can still develop in chronic hepatitis B (CHB) patients undergoing NA treatment. 2 , 4 , 5 A 10-year follow-up study conducted in Europe revealed the occurrence of new HCC cases even after more than 5 years of NA treatment. 6 Thus, it is essential to stratify the risk of HCC in patients with HBC.…”
Section: Introductionmentioning
confidence: 99%
“…A general consensus suggested using risk stratification scores in patients with GEV, which could help assess the risk of bleeding, prevent bleeding, and reduce the mortality of patients [ 6 ]. The hepatic venous pressure gradient is an important for stratifying liver cirrhosis patients, which can predict hypertension-related portal circulation complications [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%